1987
DOI: 10.1111/j.2042-7158.1987.tb05129.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ibuprofen and indomethacin on human plasma melatonin

Abstract: Ibuprofen reduced human plasma melatonin (MT) after 2 h when administered orally (400 mg) at 2400 h. Increasing plasma concentrations correlated well with increasing inhibition of serum MT levels during this time. Maximum plasma ibuprofen coincided with minimum plasma MT in 3 out of 4 volunteers. Although two volunteers exhibited a partial recovery in MT levels, concentrations after 6 h were significantly less than 0600 h values in drug-free volunteers. Administration of ibuprofen (400 mg) at 1800 h delayed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 17 publications
0
9
0
2
Order By: Relevance
“…The physiology underlying indomethacin responsivity are still unknown. Theories proposed have included a drug‐related decrease in cerebral blood flow, reduction in cerebrovascular permeability, decrease in cerebrospinal fluid pressure, effect on melatonin pathway, and an antagonist effect on nitric oxide 6‐10 …”
Section: Commentsmentioning
confidence: 99%
“…The physiology underlying indomethacin responsivity are still unknown. Theories proposed have included a drug‐related decrease in cerebral blood flow, reduction in cerebrovascular permeability, decrease in cerebrospinal fluid pressure, effect on melatonin pathway, and an antagonist effect on nitric oxide 6‐10 …”
Section: Commentsmentioning
confidence: 99%
“…1994), beta-blockers (Cowen et al 1985, and with respect to pain: anti-inflammatory drugs (Surrall et al 1987;Murphy et al 1994). Drugscreening in urine included benzodiazepines, barbiturates, cannabinoids, amphetamines, cocain and opiates.…”
Section: Study Populationmentioning
confidence: 99%
“…Special care was taken that subjects did not take any substances which are known to interfere with melatonin production and/or secretion, but which, among the general population, are sometimes not considered to be "medication," e.g., with respect to sleep: benzodiazepines (McIntyre et al 1988), antidepressants (Skene et al 1994), beta-blockers (Cowen et al 1985, and with respect to pain: anti-inflammatory drugs (Surrall et al 1987;Murphy et al 1994). Drugscreening in urine included benzodiazepines, barbiturates, cannabinoids, amphetamines, cocain and opiates.…”
Section: Study Populationmentioning
confidence: 99%
“…Thus, NSAIDS have the ability to reduce melatonin synthesis. For example, it has been shown that NSAIDs such as aspirin (Murphy et al, 1986) and ibuprofen (Surrall et al, 1987;Murphy et al, 1986) reduce melatonin synthesis in humans. However, in the present study, tolmetin, but not sulindac, increases the amount of melatonin produced by the rat pineal gland.…”
Section: Discussionmentioning
confidence: 98%